Out Come of Knee Arthrodesis with Ilizarov Method (Journal of Pakistan Orthopaedic Association, 2019)
Objectives: To determine the functional and radiological outcome of arthrodesis of the knee using the Ilizarov method.Methods: This descriptive study was conducted in Bolan Medical Complex Hospital Quetta and National Institute of Rehabilitation Medicine Islamabad from January 2016 to January 2019.All patients meeting the inclusion criteria were operated with Ilizarov for knee arthrodesis. Clinical evaluation was conducted at follow up with assessment of post-operative pain and patient’s ability to ambulate. Progressive bone fusion and limb alignment were evaluated on serial radiographs. The criterion for a complete arthrodesis was bone bridging on at least two views.Results: The total number of patients in our study were 11 with mean age 35.2 ± 13.6(range 23 to 70) years. All the patients were male. The indications for arthrodesis were post-polio fixed flexion contracture of the knee in 3(27.3%) patients, failed knee arthrodesis with other methods in 2(18.2%),sever knee trauma in 2(18.2%),sever knee pain in 1(9.1%),tuberculosis of knee in 1(9.1%), septic arthritis in 1(9.1%) and Charcot arthropathy in 1 (9.1%) patient. Patients were allowed to had partial weight bearing day after surgery. Full weight bearing was allowed a mean of 145 days (range105-195 days). The average follow up from frame removal was 21 months (range, 12-24months). In all 11(100%) a stable arthrodesis clinically and radiologically was achieved after a mean Ilizarov external fixator time of 147days (range120-195 days). Minimal complications were noted despite early weight bearing and no further surgeries were required.Conclusion: Knee arthrodesis with Ilizarov resulted in stable arthrodesis and pain free mobility. The technique offers several advantages compared with other arthrodesis methods because of fixation versatility, stability and early weight bearing. It had a high union rate and minimal post-operative complications.